Фактори розвитку культури професійного діалогу фахівця медичної галузі - Орел-Халік, Юлія Владиславівна; Орел-Халик, Ю. В.; Orel-Halik, Yu. (Запоріжжя : КПУ, 2015)
В статті висвітлено проблему розвитку культури професійного діалогу фахівця медичної галузі. Розглянуто сучасний погляд на культуру професійного спілкування фахівця медичної галузі. Проаналізовано концептуальні положення та підходи щодо формування культури діалогу. В статье освещена проблема развития культуры профессионального диалога специалиста медицинской отрасли. Рассмотрен современный взгляд на культуру профессионального общения специалиста-медика. Проанализированы концептуальные положения и подходы к формированию культуры диалога. The article outlines the conceptual approaches in the training of future specialists of medical branch. The article deals with the urgent demand of the society for specialists, who aren’t just well-educated in the medical sphere, but also have got the high level of cultural training. It was determined that the formation of cultural professional communication dominates in the process of training of future medical workers. In order to understand the meaning of the term “cultural professional dialog”, the scientific works of well-known Ukrainian and foreign pedagogics were investigated. “Cultural professional dialog” is the part of general human culture. The items of pedagogical process of training of medical specialist are: humanization of professional education; personally-oriented forms and means of training and education; active approach to training; axiological approach to the content of the educational process; communicative approach to learning; promotion of human desire acme; creative adoption of cultural dialogue to specific conditions and requirements. “Medical worker’s cultural professional communication” is a complex of social, psychological and pedagogical phenomenon that should be considered as an integrated unity of some structural components of personality. The development of specialized medical knowledge in harmony with professionally important personal qualities (moral, spiritual, ethical, communicative) gives the possibility to achieve the best results in professional training of medical staff. It is also emphasized in the article that all educational subjects should be aimed at the development of cultural professional communication of medical students. The effective formation of cultural professional communication of medical student will make it possible to solve the contradictions between social, educational and professional training of specialists.
Факторы развития культуры профессионального диалога у специалиста медицинской отрасли
Factors of the development of professional culture dialogue of medical branch experts
Keywords: культура профессионального общения; культура диалога; коммуникативная культура; профессиональная подготовка; culture of professional communication; culture of dialogue; professional training; communicative culture; культура діалогу; культура професійного спілкування; комунікативна культура; фахова підготовка